Introduction to Counting Symbols in Early Childhood with Stick Math (STIKMA) Educational Tool Games - Simatupang, Nurhenti Dorlina; Sholichah, Sefy Amaliatus; Simanjuntak, Irena Agatha (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
This research aims to improve the ability to recognize the number symbols 1-10 using the Stick Math educational game tool (ETG STIKMA). This research method uses a quasi-experimental design with a control group to test the effectiveness of using ETG STIKMA on the ability to recognize numbers. ETG STIKMA learning media has been tested by material experts and media experts who are experienced and competent in their fields. Data collection techniques use questionnaires and observation. The material expert's validation results were 80%, then the media expert gave a result of 97%, which means that the media and materials contained in STIKMA media are suitable for use to improve the cognitive abilities of children aged 5-6 years at Fatimah Az-Zahro Kindergarten. The effectiveness test results show that children's cognitive abilities in recognizing numbers 1-10 have increased by 10.50% with a positive rating of 210.00. So, this game is appropriate and efficient for improving cognitive abilities regarding the number symbols 1-10. Keywords: educational tool games (STIKMA), counting symbol, early childhood References: Aziza, A., Pratiwi, H., & Ageng Pramesty Koernarso, D. (2020). Pengaruh Metode Montessori dalam Meningkatkan Pemahaman Konsep Matematika Anak Usia Dini di Banjarmasin. Al-Athfal : Jurnal Pendidikan Anak, 6(1), 15–26. https://doi.org/10.14421/al-athfal.2020.61-02 Diningrat, S. W. M., Janah, L., & Mardiyah, S. (2019). Modified Bottle Cap for Improving Children’s Arithmetic Ability. JPUD - Jurnal Pendidikan Usia Dini, 13(2), 249–263. https://doi.org/10.21009/jpud.132.04 Fathonah, R. N., & Syafdaningsih. (2021). Video Kegiatan Rote Counting dan Rational Counting untuk Menstimulasi Berhitung Permulaan pada Anak Usia (4-5) Tahun. Tumbuh Kembang : Kajian Teori Dan Pembelajaran PAUD, 8(2), 163–174. https://doi.org/10.36706/jtk.v8i2.14630 Guslinda, K. R. (2018). Media Pembelajaran Anak Usia Dini. Jakad Publiser. Hasanah, U. (2019). Penggunaan Alat Permainan Edukatif (APE) Pada Taman Kanak-Kanak Se-Kota Metro Lampung. AWLADY : Jurnal Pendidikan Anak, 5(1), 20–40. https://doi.org/10.24235/awlady.v5i1.3831 Hayati, Z. (2019). Penggunaan Alat Permainan Edukatif (APE) Dari Botol Plastik Dan Koran Bekas Untuk Meningkatkan Kreatifitas AUD. AWLADY : Jurnal Pendidikan Anak, 5(1), 56–79. https://doi.org/10.24235/awlady.v5i1.3457 Herwegen, J. Van, Costa, H. M., Nicholson, B., & Donlan, C. (2018). Improving Number Abilities In Low Achieving Preschoolers: Symbolic Versus Non-Symbolic Training Programs. Research in Developmental Disabilities, 77, 1–11. https://www.sciencedirect.com/science/article/abs/pii/S0891422218300647?via%3Dihub Indrawati, R., Darmawani, E., & Padilah. (2021). Penerapan Metode Pemberian Tugas terhadap Kemampuan Mengenal Bilangan pada Anak Usia Dini. PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 4(2), 45–52. https://doi.org/10.31849/paud-lectura.v5i02.8736 Kesicioğlu, O. S. (2021). Investigation of Counting Skills of Pre-School Children. International Journal of Progressive Education, 17(4), 262–281. https://doi.org/10.29329/ijpe.2021.366.16 Lee, J., & Md-Yunus, S. (2015). Investigating Children’s Abilities to Count and Make Quantitative Comparisons. Early Childhood Education Journal, 44(3), 255–262. https://doi.org/10.1007/s10643-015-0707-4 Lu, Y., Li, Q., Patrick, H., & Mantzicopoulos, P. (2021).